Numerical study of the effect of infilling material in a hole-like flaw on acoustic emission characteristics and damage evolution in sandstone - Zhang, Qi; Ma, Chun-Chi; Jiang, Yalong; Geng, Huale (Frontiers in Earth Science, 2023)
To investigate the effects of infilling material of hole-like flaw, including infilling strength, stiffness, and shape, on the mechanical properties and fracture evolution of rock, a series of uniaxial compression tests are conducted on sandstone specimens. The boned-particle model (BPM) and acoustic emission (AE) techniques are adopted to study the cracking processes and AE characteristics of sandstones. The results indicate that the relatively rigid infilling can improve the mechanical properties significantly. The AE simulation in the BPM is capable of revealing the fracture evolution, and there is a good consistency between the fracture evolution and AE events. The cracking process and crack type around the hole-like flaw are influenced by the infilling type and its shape due to changes of the stress state around the hole-like flaw. The tensile cracks in nature usually initiate from the top or the bottom of the hole-like flaw. The shear or compaction cracks in nature prefer to initiate within the infilling material or from the lateral sides of the hole-like flaw. The cracking processes of rocks can be characterized by the b-value, the variation of which is comparable with the fracture behaviors and energy dissipation.